Reflection on the Significance of Kristijonas Donelaitis and His Works in the Lithuanian Press. Efforts to Commemorate Poet's 200th Birth Anniversary - Gaidauskienė, Nida (Colloquia, 2021)
On the eve of the 200th anniversary of the birth of Kristijonas Donelaitis (January 1, 1914), in Lithuania ruled by the Russian Empire, the press of the National Democrats and Liberal Democrats covered the efforts to erect a monument in honor of the poet (the idea arose in Lithuania Minor). It criticized the work of the committee that was in charge of the initiative, which was led by conservatives. The Catholic press was very reserved in its coverage of the initiatives of the memorial. The confessional aspect of the imagined Lithuanian national identity also hindered the involvement in a project that would unite the entire nation. In Russian-administered Lithuania, the emphasis was more on publications introducing Donelaitis’s personality and works. In the beginning of 1914, Kristijonas Duonelaitis’s Writings compiled by Jurgis Šlapelis was published in Vilnius; however, no public organization or institution sponsored the book. The difficulties in organizing activities to commemorate Donelaitis experienced by the Lithuanian Scientific Society testify to the fact that the poet had not yet been perceived as a national poet in Lithuania, and that there was a lack of coordinated work. In Russian ruled Lithuania, the articles and papers about Donelaitis by Juozas Gabrys Paršaitis, Mykolas Biržiška, Petras Leonas, Ignas Jurkūnas-Seinius, and Pranas Dovydaitis were overdue.With the outbreak of the war, the ambitions of the Catholic press to introduce the legacy of Donelaitis began to emerge. Some of the texts were used during the World War I for the purpose of Lithuanian cultural education. The studies of Gabrys-Paršaitis and Biržiška became an important part of the first literature textbooks of the Republic of Lithuania.
Keywords: Kristijonas Donelaitis; anniversary; reception; press; literary historiography